Content with content: A content-based instruction approach to curriculum design and course assessment in academic English for business - Kirkham, Deak (LingBaW. Linguistics Beyond and Within, 2015)
This article reports on the successful implementation of a content-based instruction (CBI) approach to a 6-month pre-sessional academic English for business and management course at a UK university. While recognising that CBI is not a ‘cure-all’ and indeed that the approach brings with it particular issues, such as instructor competence in the content, the article argues CBI offers both significant and wide-ranging benefits as a language teaching approach and as such should be given greater prominence in the language teaching industry.